Application of the DPSIR (Drivers – Pressures – State – Impact – Response) model with a focus on technological responses to reduce greenhouse gases - Bartu Castilho Viana, Gabriela; Jesús Olortiga Asencios, Yvan (Latin American Journal of Energy Research, 2022)
Climate change is a major challenge today. It is known that the increase in the concentration of greenhouse gases, especially CO2, intensifies this problem. This increase is due to some human activities, for example, energy consumption. To understand this causal relationship, the present study aimed to apply the DPSIR (Drivers – Pressures – State – Impact – Response) cause and effect model focusing on technological responses that favor the reduction of CO2 emission and its transformation into value-added products. In this case, a systemic bibliographic search was used in the databases of scientific articles. With the application of the DPSIR, it was possible to visualize in a clearer way the driving forces that lead to the emission of CO2, pressures on the environment, change of states, impacts and, finally, the technological responses. The main technological approaches identified were carbon capture and storage (CCS) as well as its use (CCUS), the latter being related to CO2 recycling. This recycling can occur through several chemical routes, such as CO2 photocatalysis, which has a great advantage because it does not require energy addition in its process and the other route is CO2 hydrogenation, which allows obtaining a variety of products with different energy purposes. Finally, climate change is a systemic challenge that needs solutions whether public, private or technological that combine and cooperate with each other, in this sense the application of the DPSIR model can be a strategy for decision makers.
Keywords: DPSIR; CO2 reduction; Climate technologies